2022
DOI: 10.1038/s41598-022-16680-8
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effective factors in predicting diet adherence using an intelligent model

Abstract: Adhering to a healthy diet plays an essential role in preventing many nutrition-related diseases, such as obesity, diabetes, high blood pressure, and other cardiovascular diseases. This study aimed to predict adherence to the prescribed diets using a hybrid model of artificial neural networks (ANNs) and the genetic algorithm (GA). In this study, 26 factors affecting diet adherence were modeled using ANN and GA(ANGA). A dataset of 1528 patients, including 1116 females and 412 males, referred to a private clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In addition to the findings related to genetic analysis, we also observed interesting results regarding the overall utility of this approach. In dataset B, 78.27% of patients demonstrated a global adherence to dietarian changes, which is considerably higher compared to studies with non-genotyped patients (1,2,69,70). This suggests that nutrigenetic tools might also impact the efficacy of diet due to increased adherence.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to the findings related to genetic analysis, we also observed interesting results regarding the overall utility of this approach. In dataset B, 78.27% of patients demonstrated a global adherence to dietarian changes, which is considerably higher compared to studies with non-genotyped patients (1,2,69,70). This suggests that nutrigenetic tools might also impact the efficacy of diet due to increased adherence.…”
Section: Discussionmentioning
confidence: 88%
“… Mousavi et al (2022) demonstrated the effectiveness of a hybrid model that combines neural networks and genetic algorithms for predicting diet adherence. Wang et al (2020) explored another hybrid model that integrates neural networks and support vector machines to predict nonadherence in Crohn’s Disease patients by streamlining the intervention process in medicine-taking.…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare, machine learning, especially sequential models, stands at the forefront of innovation, providing new ways to analyze complex medical data and improve patient treatments. Previous research primarily concentrated on non-sequential prediction methods for adherence ( Ruff et al, 2019 ; Wang et al, 2020 ; Mousavi et al, 2022 ; Warren et al, 2022 ). This approach presents a significant limitation in treatment processes, particularly for immunotherapy that often spans extended periods, such as 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…However, novel, unbiased methodologies are required to quantify and even predict adherence to dietary recommendations. One such modality was recently developed by Mousavi et al (141), who utilized a hybrid model of artificial neural networks (ANNs) and a genetic algorithm to evaluate 26 factors potentially affecting diet adherence in a data set of 1,528 patients. The accuracy for predicting adherence to diet was 93.51%; the main features associated with this prediction were duration of marriage, weight, body mass index, weight satisfaction, lunch and dinner times, and sleep time.…”
Section: Measurements Of the Effectiveness Of Dietary Interventionsmentioning
confidence: 99%